Impacto del parque crematorio San José en la calidad del aire del corregimiento el venado de Neiva. análisis desde la perspectiva sociojurídica. (2022)
Cremation is the practice of legally cremating a dead human body through the combustion process; This activity stands out from the traditional burial because it is cheaper, since the corpse is reduced to ashes and stored in a container that the family can dispose of wherever they want. unlike the daily burial, in which the relatives of the deceased must buy or rent land in specific places for the final disposal of the remains of the deceased. Therefore, it is appropriate to carry out a detailed study on this activity. For this, it is necessary to examine the reasons that have made its use so common today. Despite this popularity, cremation has a long history, there was even a time when it was considered unclean, prohibited and punished. So in the spirit of obtaining more knowledge on the subject, a chronological analysis will be carried out from the times of its origin to the present.